الخصخصة الاقتصادية بشكل عام، إيجابياتها وسلبياتها - قنوع, نزار (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يناقش هذا البحث عدداً من القضايا المتصلة بموضوع الخصخصة الاقتصادية بشكل عام. من أهمها: استعراض مفهوم الخصخصة وبعض تعاريف الخصخصة. استعراض ومناقشة أنواع الخصخصة وأشكالها وأساليبها المختلفة دراسة تجارب بعض الدول التي اتبعت الخصخصة في الدول النامية والدول المتقدمة. تحليل أداء بعض المنشآت التي تمت خصخصتها. مناقشة إيجابيات وسلبيات الخصخصة وإمكانية الحد منها. وضع معايير وآلية تتضمن نجاح عملية الخصخصة. ثم يخلص هذا البحث إلى وضع استنتاجات وتصورات عن الخصخصة لعله من الممكن الاستفادة منها في الواقع السوري. Generally, this research discusses a number of issues related to the subject of economic privatization. In particular, it focuses on some vital topics such as: Explaining the concept of economic privatization and introducing its definitions. Presenting and discussing different types, techniques and forms of economic Privatization. Studying economic privatization experience from both developed and developing countries Analyzing the performance of some privatized firms Identifying the advantages and disadvantages of economic privatization, and highlighting the possibility of limiting the effects of its disadvantages Setting standards and mechanisms that might clarify and promote the opportunities to execute a successful process of privatization This study comes up with some suggestions about the process of economic privatization that might help in the Syrian example.